Pengaruh Motivasi Dan Kepuasan Kerja Terhadap Prestasi Pegawai Pada Dinas Peternakan Kabupaten Bima - Alimin Maulana; Muhammad Yusuf; Juwani Juwani (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to determine the influence of motivation and job satisfaction on employee performance at the Bima Regency Animal Husbandry Service. The number of samples in this study was 60 ASN with a purposive sampling technique. Data collection techniques using observation, questionnaires and literature study. Data analysis technique using multiple linear regression. The research results show that motivation has no significant effect, while job satisfaction has a significant effect on job satisfaction. However, together motivation and job satisfaction have a significant effect on employee performance at the Bima Regency Animal Husbandry Service.